Pengaruh Indeks Pembangunan Manusia, Upah Minimum Regional, dan Jumlah Penduduk Terhadap Pertumbuhan Ekonomi di Jawa Timur 2015-2022 - Rosyidah, Dinda; Saptono, Ari; Wibowo, Agus (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2024)
Economic growth is an indicator that determines the success of a region's economy. East Java is one of the provinces that has experienced problems with declining economic growth. This is evidenced by data from the Central Bureau of Statistics which shows that East Java's economic growth fluctuated throughout 2015-2022. This means that there is economic instability in East Java which is the main problem. This study aims to determine the effect of human development index, regional minimum wage, and population on economic growth in East Java. The research method used is quantitative method with multiple linear regression analysis techniques processed using Eviews-9 software. The data used in this study were obtained secondary from the East Java Central Bureau of Statistics. The number of samples used was 38 districts/cities in East Java in the 8-year research period with a total of 304. The partial results showed that the human development index had a significant positive effect, the regional minimum wage had no effect, and population had a no significant negative effect on economic growth. Simultaneously, the independent variables have a significant positive effect on economic growth and are able to influence economic growth by 11.5% while the rest is influenced by other factors that have not been studied.